PENGARUH GAYA KEPEMIMPINAN, MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PT.TERAS PURAI TANAJAYA DI DESA MENCIMAI KUTAI BARAT - Taghfirul Azhima Yoga Siswa3, Ronald James Mozes Robin Jonathan (EKONOMIA, 2020)
The purpose of this study to determine: 1) To find out the leadership style on the performance of PT. Teras Purai Tanajaya employees in Mencimai Village, Kutai Barat. 2) To find out the motivation for the performance of employees of PT. Teras Purai Tanajaya in Mencimai Village, Kutai Barat. 3) To find out the work discipline on the performance of the employees of PT. Teras Purai Tanajaya in Mencimai Village,Kutai Barat. 4) To know the style of leadership, motivation and discipline on the performance of employees of PT. Teras Purai Tanajaya in Mencimai Village Kutai Barat.Analysis tools include Validity Test, Reliability Test, Normality Test, Linearity Test, Heterokedasticity Test, Multicollinearity Test, Autocorrelation Test, Analysis of Multiple Linear Regression, R Square Test, Partial Test and Simultaneous Test. Furthermore, data processing is done to change the results data from research into a new information that can be used in making conclusions.The results of data analysis in this study indicate that the leadership style variable has a positive and significant influence on the performance of employees of PT. Teras Purai Tanajaya in Mencimai Village Kutai Barat. Work motivation variables have a positive and significant influence on the performance of employees of PT. Teras Purai Tanajaya in Mencimai Village Kutai Barat. Work discipline variables have a positive and significant influence on the performance of employees of PT. Teras Purai Tanajaya in Mencimai Village Kutai Barat. Leadership style, work motivation and work discipline have a positive and significant influence together on the performance of employees of PT. Teras Purai TanajayaÂ in Mencimai Village Kutai Barat